Unveiling the Detrimental Effects of Concentrated Soil Management: Experience of Monoculture Cultivation in Telangana, India - Srinivas Katherasala (International Journal of Agriculture System, 2025)
The relentless pursuit of increased agricultural productivity has driven the widespread adoption of synthetic chemicals in soil management. Although these chemicals undeniably enhance crop yields, their long-term environmental impacts raise significant concerns. This study examines the implications of synthetic chemical use in agriculture, emphasizing the urgent need for sustainable practices that balance productivity with environmental preservation and move beyond monoculture systems. By evaluating actual farming practices and analyzing non-regulatory policies, we highlight the challenges that our planet faces. Our investigation revealed several compelling findings: 98.2% of farmers now rely entirely on synthetic chemicals, and 87.6% have abandoned traditional tools in favor of mechanical alternatives. Furthermore, a staggering 84.8% of farmers adopted monocropping practices, particularly cotton cultivation, over the past eight years. Senior farmers, drawing on their extensive experience, expressed reservations about the effectiveness of livestock manure under current conditions. A significant 73.56% of respondents believed that livestock contributions may not produce the expected outcomes. As we explored this issue further, we recognized the urgent need to address additional contributing factors. Protecting human health and the environment requires a fundamental shift in current assumptions and practices. Therefore, we propose strategies that balance agricultural productivity and ecological sustainability, fostering a more harmonious coexistence between humans and nature.